2015
DOI: 10.1371/journal.pone.0120252
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Endoplasmic Reticulum Kinase Activation Promotes Medulloblastoma Cell Migration and Invasion through Induction of Vascular Endothelial Growth Factor A

Abstract: Evidence is accumulating that activation of the pancreatic endoplasmic reticulum kinase (PERK) in response to endoplasmic reticulum (ER) stress adapts tumor cells to the tumor microenvironment and enhances tumor angiogenesis by inducing vascular endothelial growth factor A (VEGF-A). Recent studies suggest that VEGF-A can act directly on certain tumor cell types in an autocrine manner, via binding to VEGF receptor 2 (VEGFR2), to promote tumor cell migration and invasion. Although several reports show that PERK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…Consistent with this latter role, PERK promotes tumourigenesis (Bobrovnikova-Marjon et al, 2010 ) and PERK-deficient cells display a reduced ability to form solid tumors in nude mice (Spiotto et al, 2010 ). More recently, a new role for PERK signaling in promoting cancer cell migration and invasion was proposed based on experiments evaluating the effects of moderate PERK activation on medulloblastoma cell migration and invasion (Jamison et al, 2015 ). Overall, these observations support the idea that, besides its classical role in UPR and apoptosis, following H. pylori infection, PERK expression also promotes human gastric cell migration and invasion and thus the acquisition of an aggressive phenotype.…”
Section: Endoplasmic Reticulum Stress and The Unfolded Protein Responmentioning
confidence: 99%
“…Consistent with this latter role, PERK promotes tumourigenesis (Bobrovnikova-Marjon et al, 2010 ) and PERK-deficient cells display a reduced ability to form solid tumors in nude mice (Spiotto et al, 2010 ). More recently, a new role for PERK signaling in promoting cancer cell migration and invasion was proposed based on experiments evaluating the effects of moderate PERK activation on medulloblastoma cell migration and invasion (Jamison et al, 2015 ). Overall, these observations support the idea that, besides its classical role in UPR and apoptosis, following H. pylori infection, PERK expression also promotes human gastric cell migration and invasion and thus the acquisition of an aggressive phenotype.…”
Section: Endoplasmic Reticulum Stress and The Unfolded Protein Responmentioning
confidence: 99%
“…The PERK and ATF6 arms of the UPR also induce ADAM17, a member of the ADAM (a disintegrin and metalloproteinase) family that is associated with tumor initiation and progression (75). In other brain tumors such as medulloblastoma, PERK activation increases VEGFA expression and is associated with enhanced cell migration through VEGFR2 signaling (76). However, no evidence has been reported so far that PERK promotes GBM angiogenesis and invasion.…”
Section: Upr-induced Transcription Factors In Cancer-associated Signamentioning
confidence: 99%
“…Genetic studies have demonstrated that PERK is essential in supporting tumor growth and progression via diverse mechanisms, including stimulation of angiogenesis (7)(8)(9)(10)(11)(12), potential effects on antitumor immunity (13,14), and direct increase in cancer cell viability by altering its metabolic status (15), promoting survival autophagy (16)(17)(18), and induction of prosurvival microRNAs (19). Accordingly, development of novel, potent, and selective PERK inhibitors as a means to treat cancers has been proposed (20,21).…”
mentioning
confidence: 99%